2017
DOI: 10.5852/ejt.2017.385
|View full text |Cite
|
Sign up to set email alerts
|

A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic

Abstract: A new species of the sessile deep-sea barnacle, Heteralepas (Crustacea, Cirripedia), Heteralepas gettysburgensis sp. nov., is described. The specimens were collected at a depth of 225 m at the Gettysburg Seamount on the Gorringe Bank, located in the Portuguese Exclusive Economic Zone, approximately 200 km off the southwestern coast of mainland Portugal. Extensive morphological and molecular (COI, 12S and 16S) analyses were carried out to separate the species from its nearest congeners with similar geographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 756 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Of the 18,153 records in the OBIS database (i.e., the Seamounts Online version 2005-1 data set), we only found 196 referring to barnacles, and some names of taxa are invalid from the current taxonomic schedule. Compiling from the OBIS database and other publications (Zullo and Newman, 1964;Rao and Newman, 1972;Newman, 1979;Zevina, 1981aZevina, , 1983Jones, 1993;Young, 1998aYoung, ,b, 1999Young, , 2001Young, , 2002Buckeridge, 2000Buckeridge, , 2009Southward and Jones, 2003;Stocks, 2004;Tunnicliffe and Southward, 2004;Yamaguchi et al, 2004;Southward, 2005;Mironov and Krylova, 2006;Poltarukha and Zevina, 2006;Newman and Jones, 2011;Buckeridge et al, 2013;Kolbasov et al, 2017;Lobo and Tuaty-Guerra, 2017), there are approximately 125 barnacle species distributed in seamounts up to now, including the present two new species (Supplementary Table 2), and most occurrence records focus on the seamounts in the eastern and western regions of the Pacific Ocean (Figure 1). The family Scalpellidae is the dominant group, with 31 species distributed in seamounts, and the Meteor seamounts have the greatest number of barnacle species: about 12.…”
Section: Barnacles (Thoracica) Distributed In Seamountsmentioning
confidence: 99%
“…Of the 18,153 records in the OBIS database (i.e., the Seamounts Online version 2005-1 data set), we only found 196 referring to barnacles, and some names of taxa are invalid from the current taxonomic schedule. Compiling from the OBIS database and other publications (Zullo and Newman, 1964;Rao and Newman, 1972;Newman, 1979;Zevina, 1981aZevina, , 1983Jones, 1993;Young, 1998aYoung, ,b, 1999Young, , 2001Young, , 2002Buckeridge, 2000Buckeridge, , 2009Southward and Jones, 2003;Stocks, 2004;Tunnicliffe and Southward, 2004;Yamaguchi et al, 2004;Southward, 2005;Mironov and Krylova, 2006;Poltarukha and Zevina, 2006;Newman and Jones, 2011;Buckeridge et al, 2013;Kolbasov et al, 2017;Lobo and Tuaty-Guerra, 2017), there are approximately 125 barnacle species distributed in seamounts up to now, including the present two new species (Supplementary Table 2), and most occurrence records focus on the seamounts in the eastern and western regions of the Pacific Ocean (Figure 1). The family Scalpellidae is the dominant group, with 31 species distributed in seamounts, and the Meteor seamounts have the greatest number of barnacle species: about 12.…”
Section: Barnacles (Thoracica) Distributed In Seamountsmentioning
confidence: 99%
“…In those situations, genetic tools are very useful and can help to identify species faster, easier and more accurately. The barcode region of the mtDNA gene cytochrome c oxidase I (COI-5P) is broadly used to identify and discriminate crustacean species [15][16][17], including decapods [18]. In this study, the species Pyromaia tuberculata was identified through integrative taxonomy, combining morphological and genetic approaches, which provided a robust and consistent identification of the specimens, recorded for the first time in the east Atlantic.…”
Section: Introductionmentioning
confidence: 99%